Nutrient Dynamics and Retention in Land/Water Ecotones of Lowland, Temperate Lakes and Rivers 1993
DOI: 10.1007/978-94-011-1602-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Macrophyte-related shifts in the nitrogen and phosphorus contents of the different trophic levels in a biomanipulated shallow lake

Abstract: Lake Zwemlust, a small highly eutrophic lake, was biomanipulated without reducing the external nutrient loading, and the effects were studied for four years. In this paper we pay special attention to the shifts in relative distribution of nitrogen and phosphorus in the different trophic levels and to the changes in growth limitation of the autotrophs.Despite of the high external nutrient loads to the lake (ca 2.4 g P me2 y-' and 9.6 g N m-* y-'), the effects of biomanipulation on the lake ecosystem were pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 19 publications
1
63
0
1
Order By: Relevance
“…Elodea nuttallii (Planchon) St . John, for example, stored 86% of the available N and 80% of the available P and acted as sink both for N and P and maintained a clear water state in Lake Zwemlust (van Donk et al ., 1993) . Despite the marked reduction in total phosphorus concentrations, substantial concentrations of available soluble reactive phosphorus still remain but ammonium has declined (Carvalho et al ., 1995) and recently both ammonium and nitrate have been close to undetectable in Little Mere for much of the summer (Moss et al ., 1996) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elodea nuttallii (Planchon) St . John, for example, stored 86% of the available N and 80% of the available P and acted as sink both for N and P and maintained a clear water state in Lake Zwemlust (van Donk et al ., 1993) . Despite the marked reduction in total phosphorus concentrations, substantial concentrations of available soluble reactive phosphorus still remain but ammonium has declined (Carvalho et al ., 1995) and recently both ammonium and nitrate have been close to undetectable in Little Mere for much of the summer (Moss et al ., 1996) .…”
Section: Discussionmentioning
confidence: 99%
“…The macrophyte-dominated clear water state possesses a number of feedback mechanisms for stabilizing the clear water state by provision of refuges for phytoplankton grazers against fish predation (Timms & Moss, 1984), similar linkages for periphyton grazers (Leah et al ., 1978), allelopathy (Wium- Anderson, 1987), reduction of resuspension of bottom material (Bostrom et al ., 1982), and nutrient limitation of phytoplankton through nitrogen uptake by the plants or denitrification by the microorganisms associated with them (Ozimek et al ., 1990;van Donk et al ., 1993) . Macrophytes also provide spawning grounds and refuge against cannibalization for piscivorous fish like pike, which in turn decrease zooplanktivorous and benthivorous fish density (Grimm, 1989) .…”
Section: Introductionmentioning
confidence: 99%
“…In the conditions of extremely high floodings, the whole floodplain area was inundated (Fig. 1c) and the lake became the deepest part of a single large shallow water body with mass developed submerged macrophytes (Ceratophyllum demersum L., Myriophyllum spicatum L. and Potamogeton (Van Donk et al 1993;Dokulil et al 2006), producing allelopathic substances that inhibit the growth of phytoplankton (Gross et al 2007), decreasing underwater light availability (Cattaneo et al 1998), and/or creating an environment that favors small phytoplankton taxa that are easily grazed by zooplankton (Muylaert et al 2006). Altogether, our data showed that the clear water state of the investigated lake was unstable as was expected under very high nutrient loadings (Janse et al 2008).…”
Section: Ordinationsmentioning
confidence: 99%
“…However, such clear water has not always been accompanied by spontaneous recovery of macrophyte populations. There is increasing evidence that clear and turbid water are alternative stable states at moderately high nutrient loading ) and that aquatic macrophytes can promote stability of the clear-water state by providing physical protection for grazers on the algae, by competing with the algae for nutrients and by reducing water currents and allowing suspended material to settle (Blindow et al 1993;James and Barko 1990;Moss 1990;Ozimek et al 1990; Van den Berg et al 1998;Van Donk et al 1993).…”
Section: Introductionmentioning
confidence: 98%